A STUDY OF CONSUMER ATTITUDE TOWARDS GREEN PRODUCTS - A.Tejeswari (International Journal of Research Science and Management, 2016)
Increasing awareness on the various environmental problems has led a shift in the way consumers go about their life. There has been a change in consumer attitudes towards a green lifestyle. People are actively trying to reduce their impact on the environment. However, this is not widespread and is still evolving. Organizations and business however have seen this change in consumer attitudes and are trying to gain an edge in the competitive market by exploiting the potential in the green market industry. Green marketing, while incorporating these claims, is a broader concept. It includes not only altering the advertising of a product but also a variety of activities such as altering production processes, changing packaging and modifying products. The objective of the present study is to identify consumer attitude towards green products.